Circadian abnormalities in mouse models of smith–magenis syndrome: Evidence for involvement of RAI1. Issue 7 (23rd May 2013) - Lacaria, Melanie; Gu, Wenli; Lupski, James R
Abstract Smith–Magenis syndrome (SMS; OMIM 182290) is a genomic disorder characterized by multiple congenital anomalies, intellectual disability, behavioral abnormalities, and disordered sleep resulting from an ∼3.7 Mb deletion copy number variant (CNV) on chromosome 17p11.2 or from point mutations in the gene RAI1. The reciprocal duplication of this region results in another genomic disorder, Potocki–Lupski syndrome (PTLS; OMIM 610883), characterized by autism, intellectual disability, and congenital anomalies. We previously used chromosome‐engineering and gene targeting to generate mouse models for PTLS (Dp(11)17/+), and SMS due to either deletion CNV or gene knock‐out (Df(11)17‐2/+ and Rai1+/−, respectively) and we observed phenotypes in these mouse models consistent with their associated human syndromes. To investigate the contribution of individual genes to the circadian phenotypes observed in SMS, we now report the analysis of free‐running period lengths in Rai1+/− and Df(11)17‐2/+ mice, as well as in mice deficient for another known circadian gene mapping within the commonly deleted/duplicated region, Dexras1, and we compare these results to those previously observed in Dp(11)17/+ mice. Reduced free‐running period lengths were seen in Df(11)17‐2/+, Rai1+/−, and Dexras1−/−, but not Dexras1+/− mice, suggesting that Rai1 may be the primary gene underlying the circadian defects in SMS. However, we cannot rule out the possibility that cis effects between multiple haploinsufficient genes in the SMS critical interval (e.g., RAI1 and DEXRAS1) either exacerbate the circadian phenotypes observed in SMS patients with deletions or increase their penetrance in certain environments. This study also confirms a previous report of abnormal circadian function in Dexras1−/− mice. © 2013 Wiley Periodicals, Inc.